2017
DOI: 10.1155/2017/6287015
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Myocardial Injury and Intraventricular Thrombus Associated with Aluminium Phosphide Poisoning

Abstract: Aluminium phosphide (ALP) is widely used as a fumigant pesticide. In case of ALP poisoning, it is responsible for myocardial dysfunction, related to toxic myocarditis, and hemodynamic disorders. We report a case of a 28-year-old female who had intentionally ingested ALP and was admitted with cardiogenic shock. The transthoracic echocardiography (TTE) at the time of admission showed severe global myocardial hypokinesia with the presence of a giant left ventricular thrombus. Cardiovascular magnetic resonance (CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The present study revealed that troponin I showed a negative correlation with blood pressure. El Hangouche et al (2017) study is in accordance with our results that found a negative correlation between blood pressure and troponin I and stated that ALP toxicity induced myocardial injury and release of cardiac troponin. Akhtar et al (2015) also reported hypotension and increase in troponin I level after ALP exposure.…”
Section: Discussionsupporting
confidence: 93%
“…The present study revealed that troponin I showed a negative correlation with blood pressure. El Hangouche et al (2017) study is in accordance with our results that found a negative correlation between blood pressure and troponin I and stated that ALP toxicity induced myocardial injury and release of cardiac troponin. Akhtar et al (2015) also reported hypotension and increase in troponin I level after ALP exposure.…”
Section: Discussionsupporting
confidence: 93%
“…In other studies, mortality reported was 47% and 58.6%. 19 – 21 The higher mortality in children in our study may be because cases were due to accidental exposure when AlP was used for house fumigation. In other retrospective studies in children the reported mean age of poisoning was 8.5 years.…”
Section: Discussionmentioning
confidence: 75%
“…Pro-inflammatory actions of Al have been reported in various tissues (Fogarty et al, 1998;Verma et al, 2007;Lerner, 2007;Exley, 2013;Taiwo, 2014;de Chambrun et al, 2014;Gherardi et al, 2016;Martinez et al, 2017;Hangouche et al, 2017). It is triggered by Al-induced oxidative stress and free radical production (Milnerowicz et al, 2015).…”
Section: Toxic Action or Effect Selected Referencesmentioning
confidence: 99%
“…Toxic myocarditis, myocardial hypokinesia, left ventricular thrombosis and myocardial dysfunction were reported in a case of Al phosphide intoxication (Hangouche et al, 2017). Ischemic stroke due to thrombosis in the right middle cerebral artery was reported as the delayed complication of Al phosphide poisoning (Abedini et al, 2014).…”
Section: Cardiovascular Effectsmentioning
confidence: 99%